KINERJA KEUANGAN BANK PERKREDITAN RAKYAT DAN BANK PEMBIAYAAN RAKYAT SYARIAH: STUDI KASUS DI DAERAH ISTIMEWA YOGYAKARTA - Mona Iswandari; Edy Anan (Jurnal Riset Akuntansi dan Keuangan, 2017)
This study aimed to compare the financial performance of The Conventional Rural Bank (BPR) andIslamic Rural Bank (BPRS) in special region Yogyakarta region. The sample is gotten use purposivesampling method is choosing sample that has been fulfill inclusi citeria. Study sample is gotten 70with the case study in special region Yogyakarta region in period 2012-2014. Methods of dataanalysis using Independent Samples T-Test. Test results show that there is no significant differencewhen viewed from the ratio LDR/FDR between BPR and BPRS. Second, there is significant differencewhen viewed from the ratio ROA between BPR and BPRS. Third, there is significant difference whenviewed from the ratio ROE between BPR and BPRS. Fourth, there is significant difference whenviewed from the ratio NPL/NPF between BPR and BPRS. Generally, on the aspec of likuidity,rentibilty, capital ratio and the asset quality of the Conventional Rural Bank (BPR) showed thatfinancial performance is better than the IslamicRural Bank (BPRS).Keywords: Comparison financial performance, the Conventional Rural Bank (BPR), the IslamicRural Bank, Likuidity, Rentibility, Capital Ratio, Asset quality